The criticality of financial intermediation on the South African Agro-Industrialization - Thomas Habanabakize; Mulatu Fekadu Zerihun (Cogent Economics & Finance, 2023)
Access to finance is one of the factors influencing economic activities. The current study aimed at determining the role of finance in the South African agro-industrialization relationship. To achieve the study objective, bounds testing, the autoregressive distributed lag (ARDL) and error correction approaches were applied on quarterly time series data spanning between the first quarter of 1994 and the last quarter of 2021. Additionally, an interaction term was included to assist the aforementioned models in determining linkage between agriculture and industrial outputs through farmer's access to finance. Findings revealed that agricultural output and finance are valid forecasters of the industrialization behaviour in the long-run. Access to finance leads to industrial growth while agricultural output growth causes a decline in the industrialization. Nonetheless, aggregate growth of both financial access and agricultural output are associated with industrial output in the short-run. Grounded of the study findings, this study concludes that financial access influence both agriculture and industrial output. Consequently, improving famers' financial access through financial facilities, financial intermediaries and government subsidies could be a worthwhile strategy or policy to enhance a country's industrialization. As implication of the study, obtained finding can assist in linking effectiveness of primary, secondary and tertiary economic sectors in South Africa.
Keywords: 330; Agriculture; Agro-Industrialization; finance; manufacturing; South Africa